PENGARUH MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS PENDIDIKAN PEMUDA DAN OLAH RAGA KABUPATEN BULUKUMBA - Arif, Muh Ajis; Jam'an, Andi (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2019)
AbstractThis study aims to know and describe 1) the influence of work motivation on employee performance in the Office of Education, Youth and Sports Bulukumba Regency; 2) the influence of organizational culture on the performance of employees at the Office of education, youth and sports Bulukumba regency; 3) the influence of work motivation and organizational culture together on the performance of employees at the Office of education, youth and sports Bulukumba regency. implemented for 3 months from January to March 2019, the population amounted to 43 Because the population is small, so that all members of the population are taken into a sample of all employees with a total of 43 people. The analysis method used by this research is quantitative descriptive method, with double regression testing preceded by performing validity and reliability test of each variable question as well as assumption test. The result of this study 1) Coefficient of the influence of work motivation on performance of 0.359 with a value of p = 0.032 < 0.05. This indicates that work motivation has a significant positive effect on employee performance. It can be interpreted that the better the work motivation that employees have, the performance of employees will increase; 2) The coefficient of organizational culture influence on performance is 0.324 with a value of p = 0.037 < 0.05. It can be interpreted that the better the organizational culture that employees have, the performance of employees will increase; and 3) Value F = 6.78 > T Table (1.65) and the value of sig = 0.001 < α 0.05, so that the motivation of work and organizational culture together affect the performance of employees at the Office of Education, Youth and Sports Bulukumba District. Keywords: Work Motivation, Organizational Culture, and Performance